Los costos por procesos como medio para la determinación de la rentabilidad de la caja de banano de la agrícola bananera medina castillo año 2021 - Cordillo Jaramillo, Mónica Carolina (2021)
The purpose of the research work is to determine the costs by processes and the profitability of the banana box of Agrícola Bananera Medina Castillo, to carry out the different stages of banana cultivation were investigated; maintenance of the plantation and harvest, for this information collection instruments were designed; interviews, observation, review of relevant documents. For the calculation of total production costs, the cost per process system was implemented, since this system assigns and adds the costs as production progresses, the calculation and analysis of costs is very important for the company. to classify, identify and determine costs in banana production and this serves as the basis for decision-making by management and, even when it is designed for banana exploitation, it can be used for other companies that have similar problems. In this thesis the banana is described, it contains the theoretical bases that gave support and foundation to this work; it is indicated how each of the banana production phases will be developed; The elements of the cost, managerial expenses and production cost, are defined. It contains the analysis of the information and the determination of cost per production activity, thus reaching the most important phase of our thesis, such as determining the cost per box of bananas; ending with the most important conclusions and recommendations obtained from this research. Words classes:production costs, phases of banana production. Cost accounting.